2017
DOI: 10.4172/2471-9315.1000137
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Alternaria Blight of Potatoes in Nomal Valley, Gilgit-Baltistan Pakistan

Abstract: Gilgit-Baltistan (GB) having unique geographic and climatic conditions was free from plant diseases. Since the disease resistant traditional varieties of plants have been replaced by high yielding varieties. As

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…The survey showed that early blight disease was found to be high in Gwamusawa and Bakori fields in Katsina State. This agreed with findings of Abbas (2017), who reported that early blight disease tends to be more severe in humid regions because the dew or free moisture on the foliage of potato plants can cause conidia of Alternaria to germinate within 30-40 minutes and the germ tubes arising from conidia penetrate the leaf epidermis directly through micro pores.…”
Section: Discussionsupporting
confidence: 92%
“…The survey showed that early blight disease was found to be high in Gwamusawa and Bakori fields in Katsina State. This agreed with findings of Abbas (2017), who reported that early blight disease tends to be more severe in humid regions because the dew or free moisture on the foliage of potato plants can cause conidia of Alternaria to germinate within 30-40 minutes and the germ tubes arising from conidia penetrate the leaf epidermis directly through micro pores.…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, the lowest percent disease severity in Das potato crops was reported (12%). Early blight is a significant danger to potato output in the Nomal Valley of GB, according to the findings of this study (Abbas, 2017c). Within a single cropping season, this polycyclic disease can produce several disease outbreaks.…”
Section: Early Blightsupporting
confidence: 52%
“…Early blight has been a danger to potato production in GB. The most significant occurrences have been documented in the country's Nomal Valley (Abbas, 2017c). Normal Valley is split into six Mohallahs or main sections.…”
Section: Early Blightmentioning
confidence: 99%
“…Both countries produced potato one third of all over the world. The annual report FAO described that, potato production all over the world was 388000 thousand metric tons which was increase from 333600 thousand metric tons in 2010 (Abbas, 2017). Tomato ranked second important horticultural crop all over the world but it is first one in processing crops.…”
Section: Introductionmentioning
confidence: 99%
“…Same symptoms appear on stem but the color of spot is grayish. On fruit sunken lesions appear with pink to purple line which becomes shriveled, dry having no bad smell (Abbas, 2017). Early blight disease is reported all over the world.…”
Section: Introductionmentioning
confidence: 99%